2019
DOI: 10.1128/aac.01547-19
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Treatment Provides a Competitive Advantage to Mycobacterium abscessus in a Dual-Species Biofilm with Pseudomonas aeruginosa

Abstract: The physiological factors that contribute to Mycobacterium abscessus lung infections remain unclear. We determined whether antibiotic treatment targeting a major cystic fibrosis pathogen (i.e., Pseudomonas aeruginosa) could provide the ideal conditions for the establishment of M. abscessus infection. Our data showed that P. aeruginosa inhibited M. abscessus biofilm formation under control conditions and that antimicrobial therapy selectively targeting P. aeruginosa diminished this competitive interaction, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Regarding microbial intra-kingdom interactions, the antimicrobial susceptibility of different bacterial species growing inside polymicrobial biofilms has been investigated (Pompilio et al, 2015 ; Cendra et al, 2019 ; Rodríguez-Sevilla et al, 2019 ). Cross-kingdom interactions impact on antimicrobial susceptibility is still poorly studied, but some authors have described the antimicrobial susceptibility of Candida albicans yeast in polymicrobial biofilm with Staphylococcus aureus (Harriott and Noverr, 2009 ; Kong et al, 2016 ; Rogiers et al, 2018 ) or Cutibacterium acnes (Bernard et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding microbial intra-kingdom interactions, the antimicrobial susceptibility of different bacterial species growing inside polymicrobial biofilms has been investigated (Pompilio et al, 2015 ; Cendra et al, 2019 ; Rodríguez-Sevilla et al, 2019 ). Cross-kingdom interactions impact on antimicrobial susceptibility is still poorly studied, but some authors have described the antimicrobial susceptibility of Candida albicans yeast in polymicrobial biofilm with Staphylococcus aureus (Harriott and Noverr, 2009 ; Kong et al, 2016 ; Rogiers et al, 2018 ) or Cutibacterium acnes (Bernard et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the possibility of dual biofilms (and probably polymicrobial ones) that include M. abscessus [ 55 , 110 , 111 ] represents a new challenge for the management of these patients. The relationships between the different species are not well understood yet, but the implications of this fact in the clinical management of patients could be important, and the diagnosis and antibiotic selection should consider this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro conditions that mimic the airways of CF patients appear to facilitate the establishment of M. abscessus infection, and the removal of magnesium from the environment may affect the ability of the pathogen to establish infection [ 54 ]. Moreover, some studies showed that P. aeruginosa inhibited M. abscessus biofilm formation under control conditions and that antimicrobial treatment selectively targeting P. aeruginosa decreased this competitive interaction, thereby increasing M. abscessus survival [ 55 ].…”
Section: Models Of Biofilmsmentioning
confidence: 99%
“…The physiological factors that contribute to AMR in biofilms are complex. A study on antibiotic treatment of Pseudomonas aeruginosa , a major cystic fibrosis pathogen, demonstrated that it created optimal conditions for the establishment of Mycobacterium abscessus infection [ 29 ]. The P. aeruginosa inhibited M. abscessus biofilm formation until antimicrobial therapy selectively targeting P. aeruginosa diminished this competitive interaction.…”
Section: Antimicrobial Resistancementioning
confidence: 99%